The value of a statistical life under ambiguity aversion - Nicolas Treich (Center for Economic Studies and ifo Institute (CESifo), 2008)
We show that ambiguity aversion increases the value of a statistical life as soon as the marginal utility of wealth is higher if alive than dead. The intuition is that ambiguity aversion has a similar effect as an increase in the perceived baseline mortality risk, and thus operates as the dead anyway effect. We suggest, however, that ambiguity aversion should usually have a modest effect on the prevention of ambiguous mortality risks within benefit-cost analysis, and can hardly justify the substantial ambiguity premium apparently embodied in environmental policy-making.
Keywords: D81; Q51; I18; 330; ambiguity; value-of-a-statistical-life; uncertainty; risk-aversion; willingness-topay; benefit-cost analysis; environmental risk; health policy; Wert des Lebens; Mensch; Bewertung; Risikoaversion; Willingness to pay; Sterblichkeit; Theorie